The results of conservative treatment and short transpedicular fixation at burst fractures of thoracic and lumbar spine - Radchenko, Volodymyr; Popsuishapka, Konstantin; Chekryzhev, Dmytro; Teslenko, Sergii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Multifragmentary (burst) fracture can happen in case of spine trauma under the influence of high-energy axial compression with penetration of bone fragments into spine canal and paravertebral tissues. Objective: to analyze the results of treatment of patients with burst thoracic and lumbar spine fractures who were treated by conservative therapy and surgery with short transpedicular fixation. Methods: we made retrospective analysis of 23 patients with incomplete burst fractures type A3.1 and burst split fractures type 3.2 of thoracic and lumbar spine without neurological deficiency. Patients were divided into two groups: group A (conservative treatment) and group B (surgical treatment with short transpedicular fixation). We made assessment of pain, value of kyphotic deformity, compression degree, spine canal stenosis and index of sagital balance. Results: conservative treatment is indicated for patients with burst fractures type A3.1 without neurological symptoms, spine canal stenosis (up to 10 %) and posterior ligaments damage. Method of posterior fusion with short transpedicular fixation can be recommended for the treatment of incomplete burst fractures type A3.1 and A3.2 without neurological symptoms, with reserved pedicles and fragmentation of vertebrae up to 50 % of its square. Short six screws fixation can provide incomplete deformity correction (to 5 %), stable fixation with minimal loss of correction. Conclusions: conservative and surgical methods of treatment can provide satisfactory clinical results. But X-rays analysis showed advantages of surgical treatment.